The Downfall of the Soviet Union : A Spatial Explanation - Andrey, Treyvish (Washington, DC: World Bank, 2012)
Few governments have put as much energy into the development of vast and harsh places as has Russia. History shows that equalization of economic (especially industrial) mass across space as a method of a uniform development and of town-countryside convergence was in fact a policy of defensive and political aims rather than one of economic and social progress. The Soviet policy of industrial diffusion, together with state support and price system distortions, would eventually bring the entire Soviet system down. After the USSR collapsed, the Russian Federation became part of the world market and found itself a more resource abundant but colder and less populated state. Today regions' welfare levels are no longer closely tied to economic mass in contemporary Russia and the future is not clear. Two polar visions are being debated: a reinforcement of the redistributive system based on wider sharing of oil and gas profits, versus a forced diversification of regional economies with the help of high-tech development, based on old military industrial and on new R & D activities. This decision will shape Russia's economic geography for years to come and--for a country with the largest land area in the world--it could mean the difference between decline and economic superstardom.